Experimental Performance Research of Vertical Axis Wind Turbine with Expandable Airfoil. (October 2020) - Shen, Junjie; Tang, Zhipeng; Yan, Wuseng; Chen, Peng; Zhao, Xingyu; Dong, Hongkai; Li, Wuhao; Zhang, Changcun
Abstract: In order to improve the wind energy utilization of the vertical axis wind turbine (VAWT), a new type of VAWT with expandable NACA0012 airfoil is proposed in this paper. The airfoil has opening and folding state. The airfoil is open in windward which is similar with curved blade in Savonius tubine. And it is folded in leeward which is similar with airfoil in H-type turbine. In this paper, a wind tunnel test system is designed to measure the aerodynamic performance of the new turbine and three main structural parameters of the turbine are analyzed. The structural parameters contain the maximum unilateral open angle which influence the flatten of the blade and the sweep wind area. The revolution angle of the rotor corresponding to the self-rotation open angle which influence the effective working time and the airfoil self-rotation effect on the turbine rotation. And the revolution angle of the rotor corresponding to the self-rotation folded angle of the airfoil which influence the wind resistance and impact on the turbine in rapid folding process. The results show that the maximum wind energy utilization of new turbine with appropriate airfoil structural parameters and tip speed ratio corresponding maximum wind energy utilization is higher than Savonius turbine which means the performance of the new turbine capturing wind power is better than Savonius turbine and can be more suitably used in areas with relatively barren wind resource.